Regulation of Na/Ca exchange by cytoplasmic protons modifies intracellular calcium dynamics and the cardiac response to ischemia - Rui Zhang; Xiaokang Wu; Seho Kim; Brian Kim; Catherine Xie; Devina Gonzalez; Raven Norris; Nicholas Chin; Liang Li; Scott John; Kenneth D. Philipson; Michela Ottolia; et al. (Proceedings of the National Academy of Sciences, 2025)
The cardiac sodium–calcium exchanger (NCX1) is a critical regulator of intracellular calcium (Ca) in cardiomyocytes. Although strongly regulated by pH, the role of NCX1 pH sensitivity in cardiac function and intracellular Ca regulation is not understood. We used CRISPR/Cas9 to produce a pH-resistant NCX1 mouse by replacing histidine 165 with alanine (H165A). H165A mice live into adulthood and are fertile. Comparative studies in isolated ventricular myocytes demonstrated that NCX1 current (I NCX ) was significantly inhibited by lowering pH i to ~6.5 in the wild type (WT) but was unaffected in myocytes from pH-resistant H165A mice. Similarly, in WT cardiomyocytes loaded with the Ca indicator fura-2 AM, Ca transient amplitude increased dramatically during field stimulation when pH i was lowered to 6.5, consistent with impaired Ca efflux caused by proton-mediated NCX1 inhibition. In contrast, Ca transients were unchanged by low pH i in H165A myocytes, indicating effective Ca efflux by the mutant exchanger despite acidosis. When we subjected H165A mouse hearts to ischemia/reperfusion, where cellular injury is thought to result in part from Ca accumulation and inhibition of NCX1 by ischemic acidosis, there was reduced injury and improved recovery of function compared to WT. These results reveal that maintaining NCX1 activity during ischemia, and presumably maintaining Ca extrusion, is a powerful approach to protect or precondition the heart against injury that would otherwise occur subsequently during reperfusion. We conclude that allosteric regulation of NCX1 by protons is a highly relevant physiological process that takes place in clinical settings associated with abnormally low pH, such as cardiac ischemia.